Home foreclosure, health, and mental health: a systematic review of individual, aggregate, and contextual associations. - Alexander C Tsai (PLoS ONE, 2015)
Background The U.S. foreclosure crisis intensified markedly during the Great Recession of 2007-09, and currently an estimated five percent of U.S. residential properties are more than 90 days past due or in the process of foreclosure. Yet there has been no systematic assessment of the effects of foreclosure on health and mental health. Methods and findings I applied systematic search terms to PubMed and PsycINFO to identify quantitative or qualitative studies about the relationship between home foreclosure and health or mental health. After screening the titles and abstracts of 930 publications and reviewing the full text of 76 articles, dissertations, and other reports, I identified 42 publications representing 35 unique studies about foreclosure, health, and mental health. The majority of studies (32 [91%]) concluded that foreclosure had adverse effects on health or mental health, while three studies yielded null or mixed findings. Only two studies examined the extent to which foreclosure may have disproportionate impacts on ethnic or racial minority populations. Conclusions Home foreclosure adversely affects health and mental health through channels operating at multiple levels: at the individual level, the stress of personally experiencing foreclosure was associated with worsened mental health and adverse health behaviors, which were in turn linked to poorer health status; at the community level, increasing degradation of the neighborhood environment had indirect, cross-level adverse effects on health and mental health. Early intervention may be able to prevent acute economic shocks from eventually developing into the chronic stress of foreclosure, with all of the attendant benefits this implies for health and mental health status. Programs designed to encourage early return of foreclosed properties back into productive use may have similar health and mental health benefits.